Porous Bilayer Vascular Grafts Fabricated from Electrospinning of the Recombinant Human Collagen (RHC) Peptide-Based Blend - Thi My Do (MDPI AG, 2021)
Cardiovascular diseases, including coronary artery and peripheral vascular pathologies, are leading causes of mortality. As an alternative to autografts, prosthetic grafts have been developed to reduce the death rate. This study presents the development and characterization of bilayer vascular grafts with appropriate structural and biocompatibility properties. A polymer blend of recombinant human collagen (RHC) peptides and polycaprolactone (PCL) was used to build the inner layer of the graft by electrospinning and co-electrospinning the water-soluble polyethylene oxide (PEO) as sacrificial material together with PCL to generate the porous outer layer. The mechanical test demonstrated the bilayer scaffold’s appropriate mechanical properties as compared with the native vascular structure. Human umbilical vein endothelial cells (HUVEC) showed enhanced adhesion to the lumen after seeding on nanoscale fibers. Meanwhile, by enhancing the porosity of the microfibrous outer layer through the removal of PEO fibers, rat smooth muscle cells (A7r5) could proliferate and infiltrate the porous layer easily.